2009
DOI: 10.1007/s10803-009-0885-2
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Characteristics Affect Humor Processing in Individuals with Asperger Syndrome

Abstract: The present paper aims to investigate whether individuals with Asperger syndrome (AS) show global humor processing deficits or whether humor comprehension and appreciation depends on stimulus characteristics. Nonverbal visual puns, semantic and Theory of Mind cartoons were rated on comprehension, funniness and the punchlines were explained. AS individuals did not differ to the control group in humor appreciation of visual puns. However, they had difficulty understanding and appreciating Theory of Mind cartoons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 38 publications
7
71
3
1
Order By: Relevance
“…In contrast to the study in which cartoons (line drawings) were presented to adults with AS (Samson and Hegenloh 2010), the groups in the present study did not differ in how well they could explain the punch lines of the slapstick scenes. This can be attributed to the fundamental differences in the stimulus characteristics between the studies.…”
Section: Humorous Film Clipscontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to the study in which cartoons (line drawings) were presented to adults with AS (Samson and Hegenloh 2010), the groups in the present study did not differ in how well they could explain the punch lines of the slapstick scenes. This can be attributed to the fundamental differences in the stimulus characteristics between the studies.…”
Section: Humorous Film Clipscontrasting
confidence: 99%
“…The current study clearly indicated that children with AS enjoy humorous material as much as healthy children do, if the humor elements are simple and the incongruence can be perceived independently from theory of mind requirements, inferential demands, or language abilities, as was the case in the slapstick scenes of the present study. This is in accordance with previous experimental evidence, indicating that adult individuals with AS showed reduced affective responsiveness to cartoons comprising humor elements that were semantic or theory of mind dependent in nature, but rated visual puns as funny as healthy controls did (Samson and Hegenloh 2010). Other experimental studies focusing on humor production or using jokes requiring a variety of cognitive functions to be able to recognize the humor are not directly comparable with the present experiment (Emerich et al 2003;James and Tager-Flusberg 1994;Ozonoff and Miller 1996).…”
Section: Humorous Film Clipssupporting
confidence: 93%
See 3 more Smart Citations